Improvement of chiral stationary phases based on cinchona alkaloids bonded to crown ethers by chiral modification. Issue 22 (15th October 2015) - Zhao, Jianchao; Wu, Haixia; Wang, Dongqiang; Wu, Haibo; Cheng, Lingping; Jin, Yu; Ke, Yanxiong; Liang, Xinmiao
Abstract : To improve the chiral recognition capability of a cinchona alkaloid crown ether chiral stationary phase, the crown ether moiety was modified by the chiral group of (1 S, 2 S )‐2‐aminocyclohexyl phenylcarbamate. Both quinine and quinidine‐based stationary phases were evaluated by chiral acids, chiral primary amines and amino acids. The quinine/quinidine and crown ether provided ion‐exchange sites and complex interaction site for carboxyl group and primary amine group in amino acids, respectively, which were necessary for the chiral discrimination of amino acid enantiomers. The introduction of the chiral group greatly improved the chiral recognition for chiral primary amines. The structure of crown ether moiety was proved to play a dominant role in the chiral recognitions for chiral primary amines and amino acids.